Penerapan Teknologi Sabo Pada Sungai Sungai Di Wilayah Gunung Kelud Untuk Mengurangi Sedimentasi Waduk Wlingi - Agus Sumaryono; Djudi Djudi; Dyah Ayu Puspitosari (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2011)
Wlingi Reservoir which had been operated since 1977 suffered from sedimentation problem. After the eruption of Kelud Volcano in 1990, the rate of sedimentation in Wlingi Reservoir had increased significantly.The planned total volume of the reservoir was 24 million m3, the total volume of it was 4,454 million m3 in 1998 and the volume of it in 2006 was 3,348 million m3. After the operation of the reservoir for 29 years since1977, the total volume of reservoir had reduced 86% of the initial total volume. In order to decrease the rate of sedimentation of Wlingi Reservoir, Ministry of Public Works has constructed sabo fasilities such as checkdams, groundsill, consolidation dams and lahar pockets along the lahar rivers which are originated from Kelud Volcano. Besides that, in order to maintain the volume of water in the reservoir for irrigation and hydro power plant purposes, periodical dredging has been done by “Perum Jasa Tirta I”. The sabo structures which had been already constructed at K. Putih, K. Jari, K. Semut and K. Lekso had been well functioned to control sediment discharges from the sediment sources at the slope of Kelud Volcano to the Wlingi Reservoir with the capacity of 43,15 million m3. The exsisting volume of sediment which has been deposited at the sabo structures is 29,11 million m3 and the remained spaces of the sabo structures to trap the sediment transported from the upstream is 14,04 million m3. So that the effort to decrease the rate of reservoir sedimentation has succesfully done and moreover the remained volume of sediment trap capasity at the sabosrtuctures is large enough when the debris flow occurred after the possibility of volcanic eruption in the future.